The Role Of Stakeholders On Implementing Universal Services In Vietnam - Do Manh Thai; Morten Falch; Idongesit Williams (International Telecommunications Society (ITS), 2015)
This paper examines the role of stakeholders on implementing the universal services policy in Vietnam (interval 2005-2010) in order to clarify their impact and their position on performing the policy. The stakeholder theory is employed to identify and categorize the stakeholders. The authors are to look at the role of the stakeholders such as the national government, international organizations, policy intermediaries, companies, and customers/citizens via applying the qualitative method to gather data and analyse the secondary document. The qualitative approach of interviews on some officers who participated in building up and operating the policy was also conducted. The results demonstrate that stakeholders have a huge impact on the success of the universal service policy.
Keywords: 330; universal services; stakeholders; role